HOSPITAL ENVIRONMENTAL PERFORMANCE COMPARISON IN WASTE MANAGEMENT IN JAKARTA - Soegeng Basoeki; I Made Putrawan; Susy Setiawati (Jurnal Green Growth dan Manajemen Lingkungan, 2018)
This study is a survey of the performance of the hospital environment in the field of waste management. Survey was conducted in RS. Cipto Mangunkusumo, RS. Persahabatan and RSPI Sulianti Saroso. Environmental performance of the Hospital would be good if 1) has sufficient human resources, budget management and have good facilities and adequate environmental technologies 2) Environmental regulations adhered to apply quality standards. The budget for the maintenance of waste management facilities and the recruitment of human resources outsourcing needs to be improved. Efforts to increase the motivation of the human resources environment also needs to be done in order to achieve predetermined performance targets